Worldwide distribution of blood values in elite track and field athletes: Biomarkers of altered erythropoiesis - Robinson, N.; Saugy, J.; Schütz, F.; Faiss, R.; Baume, N.; Giraud, S.; Saugy, M. (Drug Testing and Analysis, 2019)
For the first time, blood samples were collected in all athletes participating in a major sporting event of the International Association of Athletics Federations (IAAF) (Athletics World Championships 2011, Daegu, Korea). All variables obtained from blood analyses were incorporated into the individual blood profiles of each athlete for the so-called athlete biological passport (ABP). This unprecedented data collection highlighted differences for a few blood biomarkers commonly measured and reported for the ABP on some group of athletes. Subsequently, blood tests analyses for all athletes were repeated during the following World Championships (2013, Moscow, Russia). Both sets of blood tests were then used to set up the distribution of blood values for track and field athletes considering potential confounding factors such as gender, age, discipline, origin of the athlete (continental classification), and time of blood collection. Implementation of well-defined distribution of blood values will allow to improve the estimation of blood doping prevalence among a specific population of athletes in track and field.